Proximate Analysis of Dewandaru Fruit (Eugenia uniflora L.) Dried Sweets - Mazarina Devi; Soenar Soekopitojo; Laili Hidayati; Issutarti; Wiwik Wahyuni; Mansoor Abdul Hamid; Naufal Kukuh Tata Asri (Universitas Negeri Malang, 2024)
Dried sweet fruit is a diversified food product that is popular in Indonesia. Dewandaru fruit (Eugenia uniflora L.) dried sweets are expected to be a preferred and beneficial product for health. This study aimed to analyze the Proximate content of Dewandaru fruit. This experimental study utilized a Completely Randomized Design (CRD) with four different drying time treatments consisting of 4 levels (6 hours, 7 hours, 8 hours, and 9 hours) and 2 replications. Observation data were analyzed using One-way ANOVA followed by the DMRT test. The results showed that Dewandaru dried sweets with a drying time of nine hours had the highest chemical properties based on the parameters of the protein content of 3.56 percent, moisture content of 30.90 percent, ash content of 1.81 percent, carbohydrate content of 63.96 percent, fat content 0.4 percent, flavonoids 5,950.85 mg/kg, saponins 46.70 mg/kg, and tannins 242.56 mg/kg. Thus, the drying time rate affects the chemical properties of Dewandaru fruit. However, drying for 9 hours has a higher fat content than other treatments.